Studi tentang kemiskinan di Kabupaten Batang Hari dan Kabupaten Muaro Jambi - Deyra Qatrunnada Nasution; Yulmardi Yulmardi; Hardiani Hardiani (e-Jurnal Perspektif Ekonomi dan Pembangunan Daerah, 2018)
The study aims to analyze: 1) the development of poverty levels, the poverty gap index and the poverty severity index in Batang Hari Regency and Muaro Jambi Regency; 2) differences in poverty levels, poverty gap index and poverty severity index between Batang Hari Regency and Muaro Jambi Regency. The data used are secondary data for the period 2002 - 2016, sourced from the Central Bureau of Statistics of Batang Hari Regency and Muaro Jambi Regency. Data were analyzed descriptively and used the Independent Sample T-test. The results of this study found that the average poverty rate in Batang Hari Regency during the period 2002 - 2016 was 13.37%, the poverty gap index was 1.87%, and the poverty severity index was 0.44%. In the same period, the average poverty rate in Muaro Jambi District was 6.51%, with the poverty gap index of 0.82%, and the poverty severity index of 0.17%. There were significant differences in poverty levels, the poverty gap index and the poverty severity index between Batang Hari District and Muaro Jambi District.